Difficulties associated with access to training and clinical support for Reporting Radiographers – A narrative evidence synthesis. Issue 4 (November 2022) - Murphy, L.; Nightingale, J.; Calder, P.
Abstract: Objectives: This narrative synthesis of evidence identifies and explores issues that impact upon the expansion or effectiveness of Reporting Radiographers working in all diagnostic modalities within the United Kingdom (UK). The publication focuses on accessibility to training for prospective Reporting Radiographers as well as clinical support within and beyond training. Key findings: Fifteen studies informed the themes of this article, they were published between 2014 and 2021. Reporting Radiographers often found it difficult find support during training and once qualified, this was usually due to the availability and workload of supervising staff. Although resistance and obstruction were experienced by many. Concerns relating to pay, promotion and interest were expressed by some respondents whilst access to courses and finance were highlighted as areas of variance across the UK. Conclusion: Inadequate support of Reporting Radiographers is impairing expansion of the specialism, whilst impacting capability and morale. This increases risk of patient harm, delays to care and inefficiency, it also threatens the sustainability of services. Negative interactions between Reporting Radiographers and Radiologists or managers is disappointing considering development of the specialism; evidence of Reporting Radiographer effectiveness and current collaboration between Royal College of Radiologists and Society of Radiographers. Issues raised in relation to pay/promotion and litigation could be clarified with ease, this should be considered when guidance is updated. Access to finance and courses is a major barrier in some regions of the UK. Scope exists for further exploration of training. England has used grants to facilitate uptake, these may prove to be an important tool in other countries. Implications for practice: Drivers to increase recruitment should be implemented alongside measures to facilitate accessibility to training and improvements to support infrastructure.